2003
DOI: 10.1038/nm894
|View full text |Cite
|
Sign up to set email alerts
|

Imaging 26S proteasome activity and inhibition in living mice

Abstract: The ubiquitin-proteasome pathway is the central mediator of regulated proteolysis in cells, and defects in this pathway are associated with cancer and neurodegenerative diseases. To assess 26S proteasome function in living animals, we developed a ubiquitin-luciferase reporter for bioluminescence imaging. The reporter was degraded rapidly under steady-state conditions and stabilized in a dose- and time-dependent manner in response to proteasome inhibitors. Using bioluminescence imaging after one dose of the che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
169
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(175 citation statements)
references
References 21 publications
5
169
0
Order By: Relevance
“…[46] Bioluminescence Imaging of Animals Human T cell trafficking in NOD/SCID-β2m null recipients was assessed non-invasively by bioluminescence with an IVIS 100 CCD camera (Xenogen, Alameda, CA, USA) as described. [47,48] Briefly, mice were injected i.p. with D-luciferin (150 μg/g in PBS) and imaged 10 min later with the IVIS (1-60 sec exposure, binning 8, f-stop 1, FOV 15 cm).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…[46] Bioluminescence Imaging of Animals Human T cell trafficking in NOD/SCID-β2m null recipients was assessed non-invasively by bioluminescence with an IVIS 100 CCD camera (Xenogen, Alameda, CA, USA) as described. [47,48] Briefly, mice were injected i.p. with D-luciferin (150 μg/g in PBS) and imaged 10 min later with the IVIS (1-60 sec exposure, binning 8, f-stop 1, FOV 15 cm).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…The gene has been cloned and sequenced (7) and used extensively in reporter gene assays in bacteria, yeast, plant, and mammalian cells (8) for bioluminescence resonance energy transfer studies and for high throughput drug screening (9-11). Rluc provides a kinetically rapid, alternative bioluminescence signal to firefly (Photinus pyralis) luciferase and, when coexpressed, enables dual reporter readouts.A rapidly evolving area of biomedical research, use of bioluminescence as an optical marker for gene expression has been recently extended to noninvasive, real-time analysis of molecular events in intact cells and living animals (12)(13)(14). Although previous data suggested that Rluc could be used for reporter imaging in mice in vivo (15), limited utility and poor bioavailability of coelenterazine was reported in a mouse model of viral infection with an Rluc reporter strain of herpes simplex virus 1 (16).…”
mentioning
confidence: 99%
“…A rapidly evolving area of biomedical research, use of bioluminescence as an optical marker for gene expression has been recently extended to noninvasive, real-time analysis of molecular events in intact cells and living animals (12)(13)(14). Although previous data suggested that Rluc could be used for reporter imaging in mice in vivo (15), limited utility and poor bioavailability of coelenterazine was reported in a mouse model of viral infection with an Rluc reporter strain of herpes simplex virus 1 (16).…”
mentioning
confidence: 99%
“…Epoxomicin (PeptaNova, 4381), gliotoxin (Applichem, APPA7665), lactacystin (Cayman chemical company, Cas 133343-34-7), and MG132 (Sigma, C2211) were dissolved in DMSO, aliquoted, and stored at −20°C. The final concentrations of inhibitors in the assays were epoxomicin 50 mmol L −1 (Götze and Saborowski 2011), lactacystin 1 mmol L −1 , gliotoxin 100 mmol L −1 (Kroll et al 1999), and MG132 25 mmol L −1 (Luker et al 2003). Enzymatic assays were performed as described above (n = 3).…”
Section: Inhibition Assaysmentioning
confidence: 99%